(untitled) (AYUSHDHARA, 2016)
Being leading cause of death in economically developed countries and second leading cause of death in developing countries cancer become giant problem. In India, 155863 new cases will be detected by 2015 and death would be 75957 hence, there is an increase in incidence as well as mortality rate. Many efforts are taken to control the disease by scientist and health organization, but still, it is spreading swiftly. Available treatment of cancer can prolong the survival of patient, but may cause severe adverse effects and obliterated the quality of life. Even experts believe that role of chemotherapy is complex issue at the end of life. Thus ray of hope turns toward palliative care to treat the cancer. With an aim to increase the life quality of the cancer patient, author consulted the classic text of Ayurveda. It was found that the disease resembling with cancer codified in the classic text of Ayurveda in the form of Granthi and Arbuda with Shodhan (curative) and Shaman (palliative) treatment and regimen to follow Aahar, Vihar, Dincharya, Rutucharya, Sadvritta, Yoga, and Satvavajaya treatment. Integration of modern and holistic method of treatment will definitely prove boon for cancer patient and will help them to enjoy meaningful life.